Estimate of Life of Reservoirs Included in the First Phase of Development of Damodar Valley Project
To estimate the quantity of silt that settles down in the reservoir, the mon- soon inflow into the reservoir is divid- ed into three portions: Portion A — The portion of the inflow which will be stored in the reservoir for release during the dry period. This corres- ponds to storage for seasonal regulation. All silt including bed load in this portion will settle down as it gets plenty of time to do so. Portion B — The portion of the inflow which will be held back temporarily for a day or two during flood control operation. This applies to Maithon and Panchet Hill only. In an average about of the flood reserve is expected to be used in this way about 5 times during the monsoon. A portion of the silt that can settle down during this interval is to be assessed. For this purpose the average depth of water is taken at 50 ft. and the period of fall about 1